Application of Multiple Linear Regression Analysis on Academic Performance in Universities. - Nareeba, Crispus (Kabale University, 2024)
Some students can do well but do not apply themselves, while others with less ability will study extremely hard and get good grades. So, there is variability that shows up naturally. However, by looking at a large group of student's patterns, there should appear to be an estimate based on all of these different aspects of a student's past. The purpose of the study was to analyze the Application of multiple linear regression analysis on academic performance of students in Universities.